ISO 21500 and success management: an integrated model for project management - Takagi, Nilton (2022)
Purpose Projects are one of the main ways used to develop organisations and turn their strategic initiatives into a reality. To support project management, several entities (e.g. associations, institutes, etc.) provide standards, guides and project management methodologies. However, despite its wide coverage of project management knowledge areas, standards currently have no specific processes focused on planning and evaluating success. The absence of these processes can limit the vision of managers and their teams on what most contributes to the success of a project. Aiming at contributing to fill this gap, this paper proposes the integration of success management processes in the ISO 21500 standard. Design/methodology/approach To develop the integration model, a Design Science Research approach was adopted for the construction and evaluation of the resulting artefact. Findings The result is an integrated model and insights for its application in practice. The model aims to help managers and their teams to identify which success management activities need to carry out and how to integrate them with the other processes of the ISO 21500 standard. Research limitations/implications The integrated model was applied in only one project. Another limitation is the difficulty in comparing the results obtained due to the small number of works focused on success management (namely related to planning, measuring, controlling and reporting success in practice) and its integration with project management standards, guides and methodologies. Originality/value The integrated model, based on success management and the ISO 21500 standard, is an important and original contribution to understand and achieve success in projects. This promotes a new vision of balanced management, directing the management effort to the areas that effectively contribute to success in each project.